Measuring Corruption in the Irkutsk Region: A Sociological Approach - Fedotov, Dmitry; Inkizhinova, Svetlana; Shkurin, Denis (Journal of Economic Sociology, 2024)
The article examines the problems of corruption in the Irkutsk region, an industrial area located in Siberia. The Irkutsk region was chosen as the object of the study. The objective of the study is to identify the factors influencing the level of cormption in the Irkutsk region. As a hypothesis of the study, the assumption is put forward that the institutionalization of corruption processes within Russian society is currently taking place. To measure the level of cormption in the Irkutsk region, a methodology of sociological research of the level and characteristics of cormption in the region has been developed and applied. The study employed a survey method on an online panel. As a result of the study, it was found that the level of domestic cormption in the Irkutsk region, measured at 13.0% in 2022, is slightly lower compared to other Russian regions. Most often, the population faces domestic cormption when receiving free medical care and due to the need for additional payments in secondary schools. During the study, risk groups were identified among respondents with a higher probability of getting into a cormpt situation. Also, a number of characteristics were identified that increase the propensity to engage in cormpt actions, including: being male, older (55-64 years) or of retirement age (65 years +), having a high financial status, and working as an individual entrepreneur, farmer or manager. It was found that the amount of business conuption in the Irkutsk region was 21.4% among the respondents representing business. The study reveals the purposes behind cormption actions committed by business representatives. It shows that cormption in the Irkutsk region is deeply entrenched in the form of a social institution, characterized by institutional components such as informal norms and mechanisms of coercion that compel adherence to cormpt practices. The obtained scientific results can be used to inform the implementation of the state anti-cormption policies.